How concept familiarity and experience with scientific argumentation are related to the way groups participate in an episode of argumentation. Issue 9 (15th March 2018) - Grooms, Jonathon; Sampson, Victor; Enderle, Patrick
Abstract: Scientific argumentation, as conceptualized in the literature, emphasizes the importance of students' social and epistemic interactions for the purposes of developing and critiquing knowledge. Students, therefore, must understand the scientific criteria for evaluating the quality of argumentative structures and interactions. Yet, a question remains as to how students' knowledge about a science concept influences their ability to productively engage in argumentative discourse about a topic. This study explored several hypotheses related to the interaction between the depth of students' familiarity with content involved in an argumentative interaction and their understanding of the scientific practice itself. Multiple triads of students completed a set of two argumentation tasks at two times during the year, in between which students had the opportunity to learn about scientific argumentation and one of the two chemistry concepts focused on in the tasks. Video records of the students' discussions were analyzed to determine the quality of their argumentation. The results indicate that a positive relationship does exist between content familiarity and high quality argumentation, especially as it relates to students epistemic and social interactions. Additional analyses suggest that students can also take up and use epistemic characteristics of scientific argumentation in contexts where the science content is unfamiliar. Further results and their implications are discussed.